2016
DOI: 10.2174/1874192401610010158
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Myocardial Bioenergetics in HFpEF and the Role of Antioxidants

Abstract: Heart failure with preserved ejection fraction (HFpEF) is a significant cardiovascular condition for more than 50% of patients with heart failure. Currently, there is no effective treatment to decrease morbidity and mortality rates associated with HFpEF because of its pathophysiological heterogeneity. Recent evidence shows that deficiency in myocardial bioenergetics is one of the key pathophysiological factors contributing to diastolic dysfunction in HFpEF. Another known mechanism for HFpEF is an overproductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Energy metabolism is central and the most important function in more metabolically active tissues, such as heart and brain. , Glucose aerobic metabolism plays a potential role in ATP production and maintains diverse biochemical processes in cardiomyocytes and neurons. , Epidemiological, clinical, and experimental evidence strongly supports that impaired bioenergetics generally occurs in myocardial and cerebral ischemia diseases and subsequent reperfusion injuries. Undoubtedly, the enhancement of energy metabolism has been a potential strategy for improving physical endurance and reducing pathological injury to protect cardiac and neuronal functions.…”
Section: Introductionmentioning
confidence: 99%
“…Energy metabolism is central and the most important function in more metabolically active tissues, such as heart and brain. , Glucose aerobic metabolism plays a potential role in ATP production and maintains diverse biochemical processes in cardiomyocytes and neurons. , Epidemiological, clinical, and experimental evidence strongly supports that impaired bioenergetics generally occurs in myocardial and cerebral ischemia diseases and subsequent reperfusion injuries. Undoubtedly, the enhancement of energy metabolism has been a potential strategy for improving physical endurance and reducing pathological injury to protect cardiac and neuronal functions.…”
Section: Introductionmentioning
confidence: 99%
“…Microvascular inflammation, endothelial activation, reduction in nitric oxide, adenosine triphosphate, and cyclic guanosine monophosphate all together lead to microvascular ischemia, LV remodeling, and fibrosis. [ 31 , 32 ] Medications (e.g., chloroquine and hydroxychloroquine) used for long term in patients with SLE causes deficiency in lysosomal cells that lead to intracellular accumulation of glycogen and membrane phospholipids, inducing cardiac structural and functional abnormalities and possibly leading to HF. [ 33 ] Moreover, thrombotic microvasculopathy, attributed to antiphospholipid antibodies, is responsible for myocardial ischemia, even in the absence of obstructive CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of Q10, L -arginine, and VD alone on the cardiovascular system is well known. Q10 is an integral component of the mitochondrial respiratory chain for ATP production as well as an antioxidant agent, thus it could assist in improving myocardial function in HF patients [52]. In addition, a meta-analysis on coenzyme Q10 randomized clinical trials showed that it improves the outcomes of HF patients.…”
Section: Discussionmentioning
confidence: 99%